Factors Influencing Millennial Generation Investment Decisions: Focus on Investment Behaviour: Faktor-Faktor yang Mempengaruhi Keputusan Investasi Generasi Milenial: Fokus pada Perilaku Investasi - Pratiwi, Fazura Mutiara; Puspawati, Dewita (Universitas Muhammadiyah Sidoarjo, 2022)
The Covid-19 pandemic has hit all corners of the world so far. The impact of Covid-19 is affecting the economy in various countries around the world. One of the reasons for the decline in the Indonesian economy is the decline in people's purchasing power, which in the end brings very bad consequences for the world economy, including Indonesia, especially when viewed from the side of tourism, trade and investment. During the pandemic, many people hold back their money to invest. Not infrequently the millennial generation is characterized as a generation that has consumptive behavior and tends to have poor financial management. However, in recent years the millennial generation has begun to realize the importance of managing short-term or long-term finances by saving or investing. The purpose of this study is to analyze and test the effect of Overconfidence Bias, Representative Bias, Regret Aversion, Mental Accounting, and Herd Behaviour on investment decisions in the millennial generation. The population in this study is the millennial generation with the characteristics of having invested. The method in this study used a survey method using a questionnaire. The sampling technique used was convenience sampling and got a sample of 145 respondents. The data was processed using SPSS 25. Testing using multiple linear regression equations. The value of Adj.R2 is 0.123, which means that these variables have an effect on investment decisions of 12.3%. The results showed that the Overconfidence Bias variable had a positive effect on investment decisions, while Representative Bias, Regret Aversion, Mental Accounting, and Herd Behaviour had no significant effect on investment decisions.